Edukasi Akuntansi Dasar dan Pembukuan Sederhana Bagi Ibu Rumah Tangga di Kelurahan Pantai Amal - Yohanna Thresia Nainggolan; ferica Christinawati Putri; Sulistya Rini Pratiwi; Meylin Rahmawati; Rizky Agusrianti Irna (CV. Multi Kreasi Media, 2022)
The purpose of this community service activity is to provide basic accounting education and simple bookkeeping for housewives in the Pantai Amal Village. This training is also targeted to provide financial management knowledge, so that household finances are always sufficient and can have savings or investments for future needs and can generate prosperity for the family. The service method carried out is in the form of dissemination and training on family financial management, briefly and clearly, using the household financial management module. There were 10 participants in this activity, namely housewives in the Pantai Amal Village. The activity begins with the provision of material, followed by a question and answer session between the presenter and the participants. Then the participants practise or practise about the material that has been given. From the research conducted, it shows that 88% of the participants are satisfied and able to understand the material, which means that this community service activity is categorised as successful.